Analisis Knowledge Creation dalam Institusi Pendidikan dan Pelatihan - Denny Gunawan; Teguh Kurniawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to analyze the knowledge creation process and the obstacles faced by the Ministry of Manpower's Employee Training and Education Center in terms of the SECI Nonaka approach. The research was conducted using a qualitative method, using analysis of literature studies on journals, books, and news about knowledge creation analysis, especially related to education and training institutions. The results of the analysis obtained three model approaches that can be used as a reference in analyzing the knowledge creation process. The first model is Soo's knowledge creation model, the second model is the Boisot model, and the third model is the SECI Nonaka model which emphasizes the creation of new knowledge in the organization through the conversion of tacit and explicit knowledge with the dimensions of Socialization, Externalization, Combination and Internalization. In conclusion, education and training require an appropriate learning model to determine potential participants who need to take part in the training, what materials and skills are needed, determine which instructors will provide training material, manage in-class learning mechanisms, and lesson plans. Therefore, the authors present three model approaches that can be used as a reference in analyzing the knowledge creation process. Keywords: Knowledge Creation, Education and Training, Labor